RIGHT TO EDUCATION OF CHILDREN IN CONFLICT WITH THE LAW AT LEMBAGA PEMBINAAN KHUSUS ANAK (LPKA) CLASS II JAKARTA, INDONESIA - Farah Fadhilah; M. Ya’kub Aiyub Kadir (Universitas Syiah Kuala, 2021)
The protection of the right to education for Children in Conflict with the Law in Indonesia in relation to International Human Rights Law is quesionable. This paper explores the fulfillment of the right to education in LPKA Jakarta towards Children in Conflict with the Law from January 2018 to March 2020. This shows that the education rights for minor offenders are in line with International Human Rights Law; however, minor offenders at LPKA Jakarta have not been able to receive Formal as well Non-Formal Education. The Indonesian legislator needs to revise the National Education System to accommodate a provision regarding the formal education for children in minor offenders; and full supports to fulfill the right to education at the LPKA Jakarta is required. Keywords: Right to Education, Children in Conflict with the Law, LPKA Jakarta.